Skeletal anomaly assessment in diploid and triploid juvenile Atlantic salmon (Salmo salar L.) and the effect of temperature in freshwater - Amoroso, Gianluca; Adams, M B; Ventura, T; Carter, C G; Cobcroft, J M (Journal of Fish Diseases, 2016)
Triploid Atlantic salmon tend to develop a higher prevalence of skeletal anomalies. This tendency may be exacerbated by an inadequate rearing temperature. Early juvenile all-female diploid and triploid Atlantic salmon were screened for skeletal anomalies in consecutive experiments to include two size ranges: the first tested the effect of ploidy (0.2–8 g) and the second the effect of ploidy, temperature (14 °C and 18 °C) and their interaction (8–60 g). The first experiment showed that ploidy had no effect on skeletal anomaly prevalence. A high prevalence of opercular shortening was observed (average prevalence in both ploidies 85.8%) and short lower jaws were common (highest prevalence observed 11.3%). In the second experiment, ploidy, but not temperature, affected the prevalence of short lower jaw (diploids > triploids) and lower jaw deformity (triploids > diploids, highest prevalence observed 11.1% triploids and 2.7% diploids) with a trend indicating a possible developmental link between the two jaw anomalies in triploids. A radiological assessment (n = 240 individuals) showed that at both temperatures triploids had a significantly (P < 0.05) lower number of vertebrae and higher prevalence of deformed individuals. These findings (second experiment) suggest ploidy was more influential than temperature in this study.